Against the currant - Matthews, Olivia (Spice Isle Bakery mystery, 2023)
"When the disgruntled owner of a rival bakery is murdered after getting a rise out of her, Lyndsay Murray, the owner of Spice Isle Bakery, falls under suspicion and most prove her innocence while dealing with her overprotective and meddlesome family"--